1998
DOI: 10.1021/bi972776r
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phospholipase D2:  Selective Inhibition of Mammalian Phospholipase D Isoenzymes by α- and β-Synucleins

Abstract: Two widely expressed mammalian phosphatidylcholine (PC)-specific phospholipases D (PLD), PLD1 and PLD2, have been identified. Recombinantly expressed PLD2 has high basal activity and is insensitive to GTP-binding protein activators of PLD1 [Colley, W. C., et al. (1997) Curr. Biol. 7, 191-201]. To investigate the regulation of PLD2 we isolated PLD2, from mouse brain by immunoaffinity chromatography. The native and recombinant proteins have indistinguishable properties: PLD2 is potently activated by phosphoinosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
282
3
8

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(306 citation statements)
references
References 44 publications
10
282
3
8
Order By: Relevance
“…Additionally, the relatively small magnitude of PLD activation achieved with mGluR agonists when compared with PDBu in our report may re¯ect the recent observation that PLD activation by 1S,3R-ACPD is ontogenetically regulated in hippocampal slices, being highest in young animals . It is, however, of interest that the synuclein proteins, which can inhibit PLD (Jenco et al, 1998), are abundant in presynaptic terminals. Their role in presynaptic PLD regulation requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the relatively small magnitude of PLD activation achieved with mGluR agonists when compared with PDBu in our report may re¯ect the recent observation that PLD activation by 1S,3R-ACPD is ontogenetically regulated in hippocampal slices, being highest in young animals . It is, however, of interest that the synuclein proteins, which can inhibit PLD (Jenco et al, 1998), are abundant in presynaptic terminals. Their role in presynaptic PLD regulation requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unknown whether these events occur at a pre-or postsynaptic location. Furthermore, the potential control of PLD at a presynaptic location would be of particular interest as it has recently been reported that synucleins (Jenco et al, 1998) and synaptojanin (Chung et al, 1997), proteins located abundantly at the presynaptic terminal, can act as endogenous PLD inhibitors, implying that PLD action at the presynaptic terminal is physiologically signi®cant. The aim of our study was to examine the signal transduction pathway which links mGluRs to PLD in our presynaptic-rich rat cerebrocortical synaptosome preparation and to determine whether PKC activation, occurring secondary to PLC activation, is involved in the activation process.…”
Section: Introductionmentioning
confidence: 99%
“…In astrocytes lacking α-synuclein palmitic (16:0) and arachidonic (20:4n-6) acid uptake and metabolism is depressed through an unknown mechanism (11). Lack of α-synuclein in brain depresses 16:0 uptake and significantly alters its metabolism (29), although the impact on brain 20:4n-6 uptake and metabolism is unknown.In addition, α-synuclein modulates phospholipase C and D activities in vitro (22,(31)(32)(33), suggesting a role in lipid-mediated signal transduction. Studies in vivo also demonstrate that α-synuclein affects enzymes involved in lipid metabolism, because α-synuclein overexpression leads to phospholipase D inhibition in yeast (34) and down regulates expression of phospholipase A 2 and of long chain fatty acid CoA synthetase in Drosophila (35).…”
mentioning
confidence: 99%
“…In addition, α-synuclein modulates phospholipase C and D activities in vitro (22,(31)(32)(33), suggesting a role in lipid-mediated signal transduction. Studies in vivo also demonstrate that α-synuclein affects enzymes involved in lipid metabolism, because α-synuclein overexpression leads to phospholipase D inhibition in yeast (34) and down regulates expression of phospholipase A 2 and of long chain fatty acid CoA synthetase in Drosophila (35).…”
mentioning
confidence: 99%
“…Animal models developed in mice and Drosophila have shown that pathological inclusions of alpha synuclein resulted in degeneration of dopaminergic neurons and motor deficits (Masliah et al 2000;Feany and Bender, 2000). In its normal context, alpha synuclein participates in diverse synaptic functions, including neuronal development, differentiation and neuroplasticity (Jenco et al, 1998;Maroteaux and Scheller, 1991;Papachroni et al, 2005). Alpha synuclein is expressed during development and maturation of dopaminergic neurons, and the protein regulates dopamine homeostasis in the adult brain by affecting neurotransmitter biosynthesis, the activity of the dopamine transporter, and presynaptic recruitment of dopamine for vesicular storage and release (Lee et al, 2001;Perez et al, 2002;Yavich et al, 2004).…”
Section: Introductionmentioning
confidence: 99%